Gastric Cancer surgery at the University Hospital of Northern Norway from 2007 to 2017, from open to minimal invasive surgery - Rosvold, Sondre (UiT Norges arktiske universitet, 2020)
Background: Gastric cancer is one of the leading causes of cancer related death, world-wide. The most common type is adenocarcinoma, which account for 95% of all gastric tube cancers. Curative treatment always includes surgery and, with few exceptions, neoadjuvant and adjuvant chemotherapy. The surgical treatment of gastric cancer has changed from open to minimally invasive surgery in many centers around the world. Minimal invasive surgery has been associated with decreased length of stay and fewer complications compared to open surgery. Our study aimed to investigate whether the introduction of minimally invasive gastrectomy for adenocarcinoma in the gastric tube was associated with similar benefits, as well as better survival rates at the University hospital of Northern Norway. Methods: Minimal invasive gastric cancer surgery was introduced at the University Hospital of Northern Norway in 2012. 170 patients admitted for curative treatment of gastric adenocarcinoma, with either minimally invasive surgery or open surgery, in the period of 2007 to 2017 were included and studied retrospectively using SPSS 26 (IBM). Results: Statistical analysis did not show a significant difference in survival using minimally invasive surgery compared to open surgery (p=0.45), nor a significant difference in survival between the two time periods (p=0.50). There was however a significant association between minimally invasive surgery and a decreased length of stay (p=0.009). Subtotal gastrectomy was associated with decreased length of stay (LOS) compared to total gastrectomy (Average LOS 8 vs. 13 days, p=0.005). There was no significant difference in severe complications between open and minimal invasive surgery (p=0.12), but significantly fewer severe complications were observed in the 2012-2017 period (p=0.007). Conclusion: This study does not show increased survival, nor a reduction in postoperative complications using minimally invasive surgery to treat gastric adenocarcinoma, compared to open surgery. A significant reduction ...